Early drug development in solid tumours: analysis of National Cancer Institute-sponsored phase 1 trials. Issue 10351 (13th August 2022) - Chihara, Dai; Lin, Ruitao; Flowers, Christopher R; Finnigan, Shanda R; Cordes, Lisa M; Fukuda, Yoko; Huang, Erich P; Rubinstein, Larry V; Nastoupil, Loretta J; Ivy, S Percy; Doroshow, James H; Takebe, Naoko
Summary: Background: The low expectation of clinical benefit from phase 1 cancer therapeutics trials might negatively affect patient and physician participation, study reimbursement, and slow the progress of oncology research. Advances in cancer drug development, meanwhile, might have favourably improved treatment responses; however, little comprehensive data exist describing the response and toxicity associated with phase 1 trials across solid tumours. The aim of the study is to evaluate the trend of toxicity and response in phase 1 trials for solid tumours over time. Methods: We analysed patient-level data from the Cancer Therapy Evaluation Program of the National Cancer Institute-sponsored investigator-initiated phase 1 trials for solid tumours, from Jan 1, 2000, to May 31, 2019. We assessed risks of treatment-related death (grade 5 toxicity ratings possibly, probably, or definitely attributable to treatment), all on-treatment deaths (deaths during protocol treatment regardless of attribution), grade 3–4 toxicity, and proportion of overall response (complete response and partial response) and complete response rate in the study periods of 2000–05, 2006–12, and 2013–2019, and evaluated their trends over time. We also analysed cancer type-specific and investigational agent-specific response, and analysed the trend of response in each cancer type over time. Univariate associations of overall response rates with patients' baseline characteristics (age, sex, performance status, BMI, albumin concentration, and haemoglobin concentration), enrolment period, investigational agents, and trial design were assessed using risk ratio based on the modified Poisson regression model. Findings: We analysed 465 protocols that enrolled 13 847 patients using 261 agents. 144 (31%) trials used a monotherapy and 321 (69%) used combination therapies. The overall treatment-related death rate was 0·7% (95% CI 0·5–0·8) across all periods. Risks of treatment-related deaths did not change over time (p=0·52). All on-treatment death risk during the study period was 8·0% (95% CI 7·6–8·5). The most common grade 3–4 adverse events were haematological; grade 3–4 neutropenia occurred in 2336 (16·9%) of 13 847 patients, lymphopenia in 1230 (8·9%), anaemia in 894 (6·5%), and thrombocytopenia in 979 (7·1%). The overall response rate for all trials during the study period was 12·2% (95% CI 11·5–12·8; 1133 of 9325 patients) and complete response rate was 2·7% (2·4–3·0; 249 of 9325). Overall response increased from 9·6% (95% CI 8·7–10·6) in 2000–05 to 18·0% (15·7–20·5) in 2013–19, and complete response rates from 2·5% (2·0–3·0) to 4·3% (3·2–5·7). Overall response rates for combination therapy were substantially higher than for monotherapy (15·8% [15·0–16·8] vs 3·5% [2·8–4·2]). The overall response by class of agents differed across diseases. Anti-angiogenesis agents were associated with higher overall response rate for bladder, colon, kidney and ovarian cancer. DNA repair inhibitors were associated with higher overall response rate in ovarian and pancreatic cancer. The rates of overall response over time differed markedly by disease; there were notable improvements in bladder, breast, and kidney cancer and melanoma, but no change in the low response of pancreatic and colon cancer. Interpretation: During the past 20 years, the response rate in phase 1 trials nearly doubled without an increase in the treatment-related death rate. However, there is significant heterogeneity in overall response by various factors such as cancer type, investigational agent, and trial design. Therefore, informed decision making is crucial for patients before participating in phase 1 trials. This study provides updated encouraging outcomes of modern phase 1 trials in solid tumours. Funding: National Cancer Institute.